Anterior Chamber Angle in Adults Born Extremely, Very, and Moderately Preterm with and without Retinopathy of Prematurity-Results of the Gutenberg Prematurity Eye Study - Achim Fieß; Sandra Gißler; Eva Mildenberger; Michael S. Urschitz; Agnes Fauer; Heike M. Elflein; Fred Zepp; Bernhard Stoffelns; Norbert Pfeiffer; Alexander K. Schuster (MDPI AG, 2022)
Purpose: To determine whether prematurity and associated factors affect the anterior chamber angle (ACA) width in adulthood. Methods: The Gutenberg Prematurity Eye Study (GPES) is a retrospective cohort study with a prospective ophthalmologic examination of adults (age 18-52 years) in Germany. All participants were examined with Scheimpflug imaging (Pentacam HR, Oculus Optikgeräte GmbH, Wetzlar, Germany) using linear regression analysis to assess the associations of ACA in the different sectors with gestational age (GA), birth weight, birth weight percentile, retinopathy of prematurity (ROP), ROP treatment, placental insufficiency, preeclampsia, and breastfeeding. Results: In total, 516 eyes of 319 preterm and full-term individuals (aged 28.9 ± 8.8 years, 188 females) were examined. ROP treatment was associated with smaller ACA width in the nasal (B = −9.6 [95%CI: −14.7; −4.5] degree; p < 0.001) and temporal positions (B = −11.5 [95%CI: −17.7; −5.3] degree; p = 0.001), whereas non-treated individuals with ROP had an unaltered ACA width, as did individuals with low gestational age without ROP. Conclusion: Advanced stages of ROP following treatment with laser- and cryocoagulation lead to a smaller ACA width until adulthood, and hence may increase the risk of angle closure in later life.